Modeling the role of the fluorine dopant in the magnetic phase diagram of LaFeAsO1-xFx superconductors - Fisher, H; Giustino, F (2012)
By using first-principles calculations we clarify the origin of the doping-induced transition from a stripe-antiferromagnetic phase to a nonmagnetic phase in LaFeAsO 1-xF x. The explicit description of the F atoms in the calculations is found to be essential for reproducing the observed phase transition. Our study shows that the concerted effects of lattice distortion and band filling arising from the dopants act to lower the energy of an unoccupied band of predominant Fe d yz character, until it crosses the Fermi level and the Fe magnetic moment is quenched. © 2012 American Physical Society.